2013
DOI: 10.1002/rra.2679
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Community Responses to Water Removal in Tropical Mountain Streams

Abstract: Mountain streams that originally supported Hawaiian cultural practices have been diverted for development, agriculture and tourism for over 150 years. Habitat characteristics and benthic macroinvertebrate community responses to water withdrawal were studied in four West Maui Mountain watersheds. We compared riffle and cascade habitats upstream and downstream of the highest‐elevation diversion in each stream and further compared streams to understand variation among watersheds. Riffles were shallow areas with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Indeed, global warming is producing a raise in temperature regimes, a reduction in ice cover and a shift in the spatial and seasonal amount of precipitations (Beniston, ; Middelkoop et al, ). Moreover, mountain lotic ecosystems are increasingly impacted by heavy flow regulation and water abstraction (Fenoglio, Bo, Cucco, & Malacarne, ; Gorbach, Shoda, Burky, & Benbow, ). Therefore, Alpine streams are changing from perennial to intermittent systems with possible but still largely unknown detrimental ecological effects (Leigh et al, ; Pinna et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, global warming is producing a raise in temperature regimes, a reduction in ice cover and a shift in the spatial and seasonal amount of precipitations (Beniston, ; Middelkoop et al, ). Moreover, mountain lotic ecosystems are increasingly impacted by heavy flow regulation and water abstraction (Fenoglio, Bo, Cucco, & Malacarne, ; Gorbach, Shoda, Burky, & Benbow, ). Therefore, Alpine streams are changing from perennial to intermittent systems with possible but still largely unknown detrimental ecological effects (Leigh et al, ; Pinna et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The alterations of the terrestrial environment as well the construction of barriers to migration change the local energy inputs as well the longitudinal connectivity among streams sections. These changes affect the organization and functions of the stream communities in the upper reaches of insular river drainages and are similar to effects initially outlined in the river continuum concept for larger watersheds (Vannote et al 1980;Tomanová et al 2008;Gorbach et al 2014).…”
Section: Resultsmentioning
confidence: 86%
“…In our study, we found that both abundance and biomass of invertebrates declined up to 20× and that caddisflies and midges were the dominant invertebrate taxa that drove these changes in biomass and abundance (Table S4). In comparison, two studies conducted on Maui Island, Hawaii, found a 44%–60% decline in invertebrate abundance and biomass as a result of flow reduction by river dams, but did not attribute the decline to certain taxa (Gorbach, Shoda, Burky, & Benbow, ; McIntosh, Schmitz, Benbow, & Burky, ). In addition, a congruent study along this rainfall gradient shows that the endemic shrimp, Atyoida bisulcata , has lower average biomass in streams with low baseflow (Tingley, ).…”
Section: Discussionmentioning
confidence: 89%
“…In comparison, two studies conducted on Maui Island, Hawaii, found a 44%-60% decline in invertebrate abundance and biomass as a result of flow reduction by river dams, but did not attribute the decline to certain taxa (Gorbach, Shoda, Burky, & Benbow, 2014;McIntosh, Schmitz, Benbow, & Burky, 2008). In addition, a congruent study along this rainfall gradient shows that the endemic shrimp, Atyoida bisulcata, has lower average biomass in streams with low baseflow (Tingley, 2017).…”
Section: Dry Wetmentioning
confidence: 96%